(untitled) (Research, Society and Development, 2023)
Microbial resistance to antimicrobials is one of the most serious health problems today, as infections caused by antimicrobial-resistant microorganisms are becoming more common. The prolonged effects of colonization or previous infection by multidrug-resistant microorganisms significantly increase the risk of infection and mortality after hospitalization, extending after hospital discharge, becoming a risk factor for the development of subsequent infections in the community or in subsequent hospitalizations. In this context, the study aims to build a prototype of an educational mobile application on multidrug-resistant microorganisms and care to be implemented after hospital discharge. This is a methodological study, with a qualitative approach and will be carried out in two distinct stages: the selection of the content of the educational technology and the elaboration of the educational technology. The content of the educational technology emerged from manuals and technical notes published by the National Health Surveillance Agency between the years 2010 and 2021. The prototype was built through the figma tool and is composed of a total of 16 screens. By using this system, patients are guided on the actions to be taken to ensure continuity of care after discharge, which optimizes the continuity and effectiveness of care. The use of technology as an educational aid tool in the care of a family member diagnosed with multidrug-resistant microorganisms facilitates the family’s understanding of the conduct and improves patients’ adherence to the treatment proposed in the hospital discharge guidance.